The Role of Genotypes That Modify the Toxicity of Chemical Mutagens in the Risk for Myeloproliferative Neoplasms - Gross-Davis, Carol; Heavner, Karyn; Frank, Arthur; Newschaffer, Craig; Klotz, Judith; Santella, Regina; Burstyn, Igor (International journal of environmental research and public health, 2015)
Background: The etiology of myeloproliferative neoplasms (MPN) (polycythemia vera; essential thrombocythemia; primary myelofibrosis) is unknown, however they are associated with a somatic mutation—JAK2 V617F—suggesting a potential role for environmental mutagens. Methods: We conducted a population-based case-control study in three rural Pennsylvania counties of persons born 1921–1968 and residing in the area between 2000–2008. Twenty seven MPN cases and 292 controls were recruited through random digit dialing. Subjects were genotyped and odds ratios estimated for a select set of polymorphisms in environmentally sensitive genes that might implicate specific environmental mutagens if found to be associated with a disease. Results: The presence of NAT2 slow acetylator genotype, and CYP1A2, GSTA1, and GSTM3 variants were associated with an average 3–5 fold increased risk. Conclusions: Exposures, such as to aromatic compounds, whose toxicity is modified by genotypes associated with outcome in our analysis may play a role in the environmental etiology of MPNs.